Association between Serum Vitamin D Level and Clinical Manifestations of Systemic Lupus Erythematous Patients in Dr. Sardjito General Hospital - Anggi Wahyu Nugroho; Ayu Paramaiswari; Deddy Nur Wachid Achadiono (Acta Interna The Journal of Internal Medicine, 2020)
Background. Vitamin D played a role in the pathogenesis of systemic lupus erythematosus (SLE). Vitamin D made dendritic cells more tolerogenic to autoantigens and inhibited B cells from producing autoantibodies. Vitamin D deficiency would make dendritic cells intolerant, increased production of interferons, and B cells produce excessive autoantibodies. These excessive autoantibodies and interferons would have caused severe clinical manifestations in SLE patients.Aims. This study was to find out vitamin D deficiency would increase the proportion of severe clinical manifestations in SLE patients in the Dr. Sardjito General Hospital. Methods. We conducted a cross-sectional study. Data was taken from medical records of SLE patients who went to Dr. Sardjito General Hospital in 2018. The independent variable was serum 25(OH) D levels, which were divided into deficiency (≤12 ng/ml) and not deficiency (>12ng/ml). The dependent variable was the clinical manifestations of SLE patients, which were divided into mild-moderate and severe. Association between two variables was analyzed using Chi-Square.Results. Vitamin D deficiency was observed in 19(54%) and not deficiency in 16(46%) subjects. SLE patients who underwent vitamin D deficiency more often experienced severe clinical manifestations than those without (52.6% versus 12.5%), prevalence ratio 4.2 CI 1.1-16.5 p=0.015. SLE patients who underwent vitamin D deficiency were more likely to suffer mucocutan, musculoskeletal, and kidney disorders. Also more likely to suffer more than 2 organ disorders than those without (57.9% versus 12.5%), prevalenceratio 4.6 CI 1.2-17.9 p=0.007.Conclusions. Vitamin D deficiency increased the proportion of severe clinical manifestations in SLE patients at Dr. Sardjito General Hospital. It also increased the proportion of mucocutan disorder, musculoskeletal disorder, and kidney disorder. Also, it increased the proportion of occurrence of more than 2 organ disorders in SLE patients at Dr. Sardjito General Hospital.